Changes in UK medical trainees' perceptions of workplace-based assessments across 10 years: results from two cross-sectional studies. Issue 1158 (15th January 2021) - Cheston, Hannah; Graham, David; Johnson, Gavin; Woodland, Philip
Abstract : Objectives: Workplace-based assessments (WPBAs) have become embedded in the training and assessment of UK medical trainees since the onset of the 21st century. When first introduced WPBA required a significant adjustment in both trainees' and educators' training behaviour, and was met with scepticism in some quarters. In this study, we aimed to evaluate how trainees' perceptions of WPBAs have evolved over a 10-year period, as experience with them has increased. Design: Two online questionnaires were constructed and distributed to UK trainees. The first was distributed in 2008, the second in 2018. Questions related to trainees' perception of WPBAs as a learning process and as a reflection of their competence. Setting and participants: All UK medical trainees were eligible to respond. In 2008, 482 trainees from 96 hospitals completed the questionnaire. In 2018, 356 trainees from 103 hospitals completed the questionnaire. Main outcome measures: Data were analysed both quantitatively and qualitatively. A comparison between the numbers of each WPBA modality completed in 2008 and 2018 was assessed using chi-squared test. Comparisons of Likert scale values between 2008 and 2018 were assessed using unpaired t-test. Thematic analysis was carried out on free-text answers. Results: The number of forms completed per participant increased significantly from 2008 to 2018. In 2008, forms were most commonly completed immediately after a learning observation (34%). In 2018, forms were most commonly completed between 1 week and 1 month after observation (58%). In 2018, significantly fewer WPBAs were followed by an educational/beneficial discussion in comparison to 2008 data. The most common free-text theme in the 2008 data set was 'supervisor issues' whereas in 2018 the most commonly noted theme was 'limited educational benefit'. Conclusions: Our study suggests trainees' perspectives of WPBAs have not changed in the 10 years since implementation. Trainees do not perceive WPBA as an accurate reflection of their competency but instead as a 'tick-box' bureaucratic exercise to enable career progression. Development of educator training and trainer and trainee job-planning is required to ensure that WPBAs are genuinely educational activities that offer an accurate reflection of trainees' medical competence.